Meta-analysis of Theory of Mind (ToM) impairment in bipolar disorder. Issue 2 (12th October 2015) - Bora, E.; Bartholomeusz, C.; Pantelis, C.
Abstract : Background: Theory of mind (ToM) dysfunction is prominent in a number of psychiatric disorders, in particular, autism and schizophrenia, and can play a significant role in poor functioning. There is now emerging evidence suggesting that ToM abilities are also impaired in bipolar disorder (BP); however, the relationship between ToM deficits and mood state is not clear. Method: We conducted a meta-analysis of ToM studies in BP. Thirty-four studies comparing 1214 patients with BP and 1097 healthy controls were included. BP groups included remitted (18 samples, 545 BP patients), subsyndromal (12 samples, 510 BP patients), and acute (manic and/or depressed) (10 samples, 159 BP patients) patients. Results: ToM performance was significantly impaired in BP compared to controls. This impairment was evident across different types of ToM tasks (including affective/cognitive and verbal/visual) and was also evident in strictly euthymic patients with BP ( d = 0.50). There were no significant differences between remitted and subsyndromal samples. However, ToM deficit was significantly more severe during acute episodes ( d = 1.23). ToM impairment was significantly associated with neurocognitive and particularly with manic symptoms. Conclusion: Significant but modest sized ToM dysfunction is evident in remitted and subsyndromal BP. Acute episodes are associated with more robust ToM deficits. Exacerbation of ToM deficits may contribute to the more significant interpersonal problems observed in patients with acute or subsyndromal manic symptoms. There is a need for longitudinal studies comparing the developmental trajectory of ToM deficits across the course of the illness.